Tax regulation of innovation activities - N. Z. Zotikov (Управление)
Under the current Western economic sanctions, one of the most important tasks facing the state is to increase the level of innovation in the national economy. Investment and innovation activity has a direct impact on the volume of production potential and, as a consequence, on the formation of budget revenues. The subject of the study is the use of methods of tax regulation of innovation in the regions. The purpose of the article is tax incentives for investment activities by the methods provided by the Tax Code of the Russian Federation (hereinafter referred to as RF, Russia) in federal districts using the example of value added tax, corporate property tax, and corporate profit tax. The following methods аre used in the study: analysis and synthesis, generalisation, grouping, the tabular one. The information base for the research are the Tax Code of the RF, reports of the Federal Tax Service of Russia on these taxes. The work examines foreign and domestic experience in applying methods and benefits to stimulate innovative business activity. The study has found that in the regions, at an extremely low level, they take advantage of the opportunities provided by the Tax Code of the RF in pursuing innovation policy, in particular, in conducting research and development, using the methods of accelerated depreciation of fixed assets, and investment tax deductions. The analytical data and conclusions obtained during the study can be used in the practical activities of regions and economic entities.